FINANCIAL RATIO ANALYSIS OF PT WIJAYA KARYA (PERSERO) TBK. DURING THE COVID-19 PANDEMIC (2020-2022) TO DETERMINE THE IMPACT OF THE PANDEMIC ON THE COMPANY'S FINANCIAL PERFORMANCE - Naufal Nurrohmat; Ikhsan Bagaskoro; Abdillah Khakim; Rizqi Fadhilah Nur Rohman; Fakhmi Zakaria (Pusat Riset dan Inovasi Nasional, 2024)
A significant decrease in profit was experienced by PT Wijaya Karya (Persero) Tbk during the Covid-19 pandemic in Indonesia, which decreased by 33.48% in 2021 and decreased by 94.13% in 2022. However, company performance cannot be measured by profit levels alone. Descriptive analysis using financial ratios such as liquidity ratios, solvency ratios, activity ratios, and profitability ratios is the basis of this research. It is concluded that the company's performance during the pandemic is not good, if the resulting financial ratio analysis is compared to the industry average standard. Average current ratio is still far below industry standards, which is 106% compared to 200%. Average quick ratio is still far below the industry standard, which is 78% compared to 150%. Average cash ratio is still far below industry standards, which is 23% compared to 50%. Average debt to equity ratio shows a value far above the industry standard, which is 312% compared to 90%, even exceeding the maximum debt to equity ratio limit of 200%. Average debt to asset ratio shows a value far above the industry standard, which is 76% compared to 35%. Average total asset turnover is still far below the industry standard, which is 0.26 times compared to 2 times. Average fixed asset turnover is still far below the industry standard, which is 2.60 times compared to 5 times. Average NPM is still far below the industry standard, which is 1.07% compared to 20%. Average ROE is far below the industry standard, at 1.08% compared to 40%.